Pengaruh Likuiditas dan Solvabilitas Terhadap Kinerja Keuangan Perusahaan Dimoderasi oleh Ukuran Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2022 - Cornelio Purwantini; Pikanti Endah Artanti; Ignatius Bondan Suratno (Jurnal Ilmiah Aset, 2026)
This study aims to determine the effect of liquidity (CR) and solvency (DAR), on the company's financial performance (ROA) moderated by and company size (ln total assets) listed on the Indonesia Stock Exchange in 2022. The population consisted of 684 non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2022. The research data is secondary data taken from the official website of the Indonesia Stock Exchange (www.idx.co.id) in December 2023. The data were analyzed using descriptive analysis, moderating regression analysis (MRA), and analysis hypothesis with SEM-PLS with WarpPLS software version 8.0 is because classical assumption testing cannot be fulfilled. The results of this study indicate that: (1) liquidity (CR) has no effect on the company's financial performance (ROA); (2) solvency (DAR) has a positive and significant effect on the company's financial performance (ROA); (3) company size (ln total assets) has a negative and significant effect on the company's financial performance (ROA); (4) company size (ln total assets) does not moderate the effect of liquidity (CR) on the company’s financial performance (ROA); and (5) company size (ln total assets) moderates the effect of solvency (DAR) on the company’s financial performance (ROA).